Cryoplasmasorption in Complex Treatment of Patients with Generalized Peritonitis - O. M. Shevtsova; N. V. Shapovalova; A. A. Lavrentyev (Общая реаниматология, 2007)
The dissatisfaction of patients having generalized peritonitis with the results of treatment and high mortality rates have induced the authors to optimize treatment policy, by introducing the cryoplasmasorption technique aimed at correcting endogenous intoxication.Subjects and methods. The study covered 67 patients with generalized peritonitis, including 29 and 38 patients having its toxic and terminal stages, respectively. According to the therapy performed, the patients were divided into 2 groups: 1) 39 received cryoplasmasorption and 2) 28 had conventional therapy. The efficiency of treatment was evaluated by the changes in a battery of clinical laboratory data including hemostasis, immunity, and intoxication indices.Results. Cryoplasmasorption was shown to have a positive impact on the homeostatic parameters under study, which could reduce mortality rates in patients with generalized peritonitis by 14%.